2020
DOI: 10.1016/j.heliyon.2020.e05405
|View full text |Cite
|
Sign up to set email alerts
|

Production of propolis and honey from Tetragonula laeviceps cultivated in Modular Tetragonula Hives

Abstract: Propolis and honey produced by stingless bees are regarded as high economic value products due to their bioactive components, which are significantly influenced by conditions at the cultivation location. This study investigated the effect of cultivation location on the amount and quality of propolis and honey produced by Tetragonula laeviceps cultivated in Modular Tetragonula Hives. Fifteen bee colonies were cultivated for at least three months in coffee plantations at two different locations, namely Cibodas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…MOTIVE units have also been developed for use with instrumentation systems. By outfitting the beehive with these instrumentation systems, beekeepers can collect microclimate data, allowing them to monitor the health of the colony with respect to the microclimate conditions within the hive [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…MOTIVE units have also been developed for use with instrumentation systems. By outfitting the beehive with these instrumentation systems, beekeepers can collect microclimate data, allowing them to monitor the health of the colony with respect to the microclimate conditions within the hive [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is a gomo-resin compound produced stingless bees by mixing salivary secretions and beeswax with exudate collected from plants [4,5]. Bees use this material to seal open spaces in the hive and protect the hive from various pathogenic agents [6].…”
Section: Introductionmentioning
confidence: 99%
“…biroi can produce honey 2,030 mL/colony for two moths meliponiculture. Furthermore, Abduh et al (2020) reported that propolis production from T. laeviceps ranges from 4.26 to 4.54 g/month, meliponiculture in Cibeusi Village (Subang, West Java). Erwan et al (2021b) reported that propolis production from honey pots of stingless bee Tetragonula sp.…”
Section: Introductionmentioning
confidence: 99%
“…is 3.28 g/month for bamboo hives and 7.40 g/month for box hives. Furthermore, Abduh et al (2020) reported production of propolis from T. laeviceps ranges from 4.26 to 4.54 g/month. Production of propolis from T. laeviceps which meliponiculture for four months ranges from 15.4 to 77.2 g (Agussalim et al 2020).…”
mentioning
confidence: 99%